Toward high‐efficiency stable 2D/3D perovskite solar cells by incorporating multifunctional CNT:TiO2 additives into 3D perovskite layer. Issue 2 (10th January 2022) - Jin, Mengqi; Li, Huilin; Lou, Qiang; Du, Qing; Huang, Qingsong; Shen, Zhitao; Li, Fumin; Chen, Chong
Abstract: The power conversion efficiency (PCE) of 2D/3D perovskite solar cells (PSCs) is still significantly low compared with 3D PSCs due to the poor charge transport ability of 2D perovskite thin films and a large number of defects in 3D thin films. Herein, to address these two issues, multifunctional TiO2 nanoparticles (NPs)‐modified carbon nanotubes (CNT:TiO2 ) additives are incorporated into 3D perovskite layer for the first time, and demonstrate three positive effects for CNT:TiO2 material application: firstly, it passivates the defect state of the 3D perovskite layer and enhances the charge mobility of the 3D layer; secondly, its interaction with the 2D film increases the conductivity of the 2D layer and produces the interface polarization electric field to promote the hole extraction. As a consequence, not only the PCE of the optimized 2D/3D PSCs with the CNT:TiO2 is greatly improved to 22.7% from 19.8% of the control PSCs, but also the stability is significantly improved. Abstract : Stable 2D/3D perovskite solar cells with efficiency 22.7% by incorporating multifunctional CNT:TiO2 additives into 3D perovskite layer.